Reader and generator for QR Codes: A Review - Singh, Utkarsh; Vaish, Nitish; Kumar, Vidhanshu; Kumar, Lokesh (Journal of Advanced Research in Applied Artificial Intelligence and Neural Network, 2023)
These days, Quick Response (QR) codes seem to be everywhere. They can be seen on advertisements in magazines, websites, product packaging, and other places. Since mobile phones have become a basic necessity for everyone, using QR codes is one of the most intriguing ways to link customers to the internet digitally. In this article, we offer a method for producing QR codes that allows users to type text into a web browser and produce the QR code. To create a user interface on a web browser and encode data in a QR Code symbol, the well-known opencv-python package was combined with the QR code module. English-language texts with one or more lines were used in the experiment.The outcome demonstrates that all QR encoding outputs were created successfully and accurately.